Relationship between tree bark surface temperature and selected meteorological elements - STŘEDA, Tomáš; LITSCHMANN, Tomáš; STŘEDOVÁ, Hana (Contributions to Geophysics and Geodesy, 2015)
The results were obtained by measurements in 2014 and 2015 in an apple orchard in Starý Lískovec and Těšetice (South Moravia, Czech Republic, Central Europe) into fertile planting of apple trees. The results show that the bark surface temperature during the year slightly differs from the surrounding air temperature. In addition, it is in average a few tenths of a °C higher in the period before the onset of the vegetation and several tenths of a degree lower during vegetation. Causes of these differences appear to be associated with the flow of sap as well as with foliage. Although it can be reasonably assumed that the temperature of the bark surface on the south side will be significantly affected by the global radiation, our measurements did not demonstrate this dependency. It appears that the wind speed had significantly larger influence on the temperature differences in the non-vegetation period as at speeds over 3.5 ms−1, the drop of temperature is so significant that the bark surface is colder than the surrounding air. Comparison of the development of sums of daily and hourly effective temperatures above 10 °C has shown that where daily values do not show significant differences, hourly values differed so prominently that the calculated date of emergence of adult codling moth in the bark surface was approximately one week earlier than with the use of data for air temperatures.